2009
DOI: 10.1177/0748233709105270
|View full text |Cite
|
Sign up to set email alerts
|

Effect of occupational exposure to elemental mercury in the amalgam on thymulin hormone production among dental staff

Abstract: Occupational exposure of dental staff to elemental mercury vapor released from dental amalgam is an issue of concern because of the possible immunological and neurological adverse outcomes. Recently, studies have reported that inorganic mercury induces immunosuppression by decreasing the production of thymus gland hormone (thymulin). This study aimed at investigating mercury body burden in dental staff and the relation of this burden to the potential impact of mercury on thymus gland hormone level (thymulin). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
2
10
0
3
Order By: Relevance
“…Likewise, group 3 possesses greater risks compared to group 2 and so on. This statistical significance of age parameter on mercury levels in individuals has been in consistence with previously reported findings [ 9 , 23 , 24 ] and in contrast to [ 25 – 27 ].…”
Section: Resultssupporting
confidence: 92%
“…Likewise, group 3 possesses greater risks compared to group 2 and so on. This statistical significance of age parameter on mercury levels in individuals has been in consistence with previously reported findings [ 9 , 23 , 24 ] and in contrast to [ 25 – 27 ].…”
Section: Resultssupporting
confidence: 92%
“…Mercury is well-known to be absorbed by the body following inhalation, with numerous occupational studies showing air levels to be correlated with internal doses estimated by urinary mercury excretion (Farahat et al, 2009;Heyer et al, 2008;Levy, 1995;Mortada et al, 2002). There is much controversy about the safety of dental amalgam as it has been demonstrated to pose occupational risks to dental practitioners and their assistants…”
Section: Discussionmentioning
confidence: 99%
“…It had been shown that inorganic mercury induces immunosuppression by decreasing the production of thymus gland hormone (thymulin) in young mice [64]. Recently, a study in human (dental staff workers, dentists, and nurses) showed a significant increases of mercury levels in urine and blood compared to nondental personnel, and a concomitant reduction of thymulin hormone and nitric oxide in blood [65]. This study confirms the findings in humans of those previously reported with laboratory animals.…”
Section: Oral Exposure To Mercury Amalgammentioning
confidence: 99%